DINAMIKA BAWASLU KABUPATEN GOWA DI TAHUN 2019 (Telaah atas Hukum Islam) - Hernita; Usman Jafar; Fadli Andi Natsir (ISTIQRA: Jurnal Hasil Penelitian, 2023)
The dynamics of BAWASLU in Gowa Regency in 2019 refer to its role and function in dealing with violations of money politics. In the explanation, the objectives of this study are to determine the effectiveness of Bawaslu, the involvement of various stakeholders in preventing money politics in elections, and to understand the perspective of Islamic legal sanctions against money politics violations. This research used is qualitative. The research approach used is the Juridical and Theological Normative (Syar'i) approach. The data sources are primary and secondary. Data collection methods used consisted of observation, interviews, and documentation. The results of this study explain that Bawaslu Kab. Gowa has been effective in supervising political practices by carrying out all main tasks, achieving goals, being on time, and having active participation by tightening supervision, especially at the campaign and voting stage by looking at the various cases that have occurred and handled according to the procedures in force. such as the case of money politics in 2019 where there were two cases recorded. Furthermore, the involvement of stakeholders in preventing the practice of money politics using coordination, starting from the police, prosecutors, and community leaders. While sanctions in the perspective of Islamic law can be understood that violations of money politics can be imposed with a finger ta'zir penalty in the form of a prison sentence. The issue of the time limit will be returned to ulil amri or the government that has the authority to decide on money politics violations.